Governing river rehabilitation projects for transformative capacity development. Issue 5 (18th October 2021) - Martel, Patrick; Sutherland, Catherine; Hannan, Sylvia
Abstract: River rehabilitation projects are framed as water security interventions in South Africa. They aim to address water quality and water quantity issues, as well as to improve socio-ecological relationships. These projects acknowledge the value of capacity building and social learning in enhancing water security. However, they adopt different governance approaches and hence have different knowledge construction and capacity building outcomes. This paper employs a 'governmentality' framework to analyse the capacity development processes within three river rehabilitation projects in Durban, South Africa. The analysis revealed that the three projects, with their different governmentalities, produced different capacity development modalities, which are utilised to sustain 'the object of intervention' in each river rehabilitation project. However, despite these differences, information as the currency of action; the context or site of learning; the importance of building state–citizen relationships; and the need for bridges or intermediaries, emerged as common elements which support capacity building and knowledge sharing across all three projects. HIGHLIGHTS: River rehabilitation projects are socio-ecological governance processes. Capacity building modalities emerge from different governmentalities of river rehabilitation projects. Locally driven river rehabilitation projects emerge through institutional voids. Sharing knowledge, understanding socio-ecological relations, state–citizen relationships and intermediaries are critical to transformative river rehabilitation projects.